Validity and reliability of a wearable fitness technology scale in Portugal - Pedragosa, Vera (2022)
Currently, the use of technological devices for monitoring physical activity and in other mobile applications is widespread among sports users and is continuously growing. The aim of this study was the validation of the reliability of the use of Wearable Fitness Technology (WFT) in the context of fitness through quantitative analysis. Data collection was conducted online during the COVID-19 pandemic period. The sample consisted of 177 members of fitness centres who used MYZONE technology in Portugal. An Exploratory Factor Analysis (EFA) (Factor v10) and a Confirmatory Factor Analysis (CFA) (AMOS v22.0) were used to test the item fit. The results showed adequate fits, identifying a total of 14 items in a single factor to assess WFT in MYZONE users in fitness centres. The reliability of the scale showed adequate indices within the indicated limits. This study extends the current literature on WFT; provides information for providers, managers, and members; and aims to improve the fitness experience by developing a valid and reliable tool to assess the characteristics and incidence of WFT in fitness centres. The complexity of the WFT will affect the degree of user engagement with the fitness centre, highlighting the importance of using staff skills to generate motivational and innovative challenges to improve the service experience. Furthermore, this scale could be used to examine the influences of WFT on managers’ and members’ perceptions of the service experience in the Portuguese context.